Electroacupuncture improves cognitive impairment in diabetic cognitive dysfunction rats by regulating the mitochondrial autophagy pathway - Xia Ge; Ling Wang; Qianqian Cui; Hongli Yan; Zhongbao Wang; Shandong Ye; Qingping Zhang; Aihua Fei (Journal of Physiological Sciences, 2022)
Abstract Background Diabetes-associated cognitive dysfunction has become a major public health concern. However, the mechanisms driving this disease are elusive. Herein, we explored how electroacupuncture improves learning and memory function in diabetic rats. Methods The diabetic model was established by intraperitoneal injection of streptozotocin (STZ) in adult Sprague–Dawley rats. Rats were fed on high-fat and high-sugar diets. Learning and memory functions were assessed using behavioral tests. The hematoxylin and eosin (H&E) staining, Western blotting, real-time PCR, ELISA, immunohistochemistry, and transmission electronic microscopy (TEM) was performed to test related indicators. Results High-fat and high-sugar diets impaired learning and memory function in rats, while electroacupuncture treatment reversed these changes. The model group presented highly prolonged escape latency compared to the control group, indicating impaired learning and memory functions. The TEM examination showed that electroacupuncture enhanced Aβ clearance and mitochondrial autophagy in hippocampal neuronal cells by increasing DISC1 expression. Conclusions Electroacupuncture improves learning and memory function in diabetic rats by increasing DISC1 expression to promote mitophagy. This enhanced Aβ clearance, alleviating cytotoxicity in hippocampal neuronal cells.